Anthropogenic increase in carbon dioxide modifies plant-insect interactions - Zavala, Jorge Alberto (2017)
Industrialisation has elevated atmospheric levels of CO2 from original 280ppmto current levels at 400 ppm, which is estimated to double by 2050. Althoughhigh atmospheric CO2 levels affect insect interactions with host plants, theimpact of global change on plant defences in response to insect attack is notcompletely understood. Recent studies have made advances in elucidating themechanisms of the effects of high CO2 levels in plant?insect interactions.New studies have proposed that gene regulation and phytohormones regulateresource allocation from photosynthesis to plant defences against insects.Biochemical and molecular studies demonstrated that both defensive hormonesjasmonic acid (JA) and ethylene (ET) participate inmodulating chemicaldefences against herbivores in plants grown under elevated CO2 atmosphererather than changes in C:N ratio. High atmospheric CO2 levels increase vulnerabilityto insect damage by down-regulating both inducive and constitutivechemical defences regulated by JA and ET. However, elevated CO2 levelsincrease the JA antagonistic hormone salicylic acid that increases other chemicaldefences. How plants grown under elevated CO2 environment allocateprimary metabolites from photosynthesis to secondary metabolism would helpto understand innate defences and prevent future herbivory in field crops. Wepresent evidence demonstrating that changes in chemical defences in plantsgrown under elevated CO2 environment are hormonal regulated and reject theC:N hypothesis. In addition, we discuss current knowledge of the mechanismsthat regulate plants defences against insects in elevated CO2 atmospheres.